Pañjābī sāhita-itihāsa dīāṃ loka-rūṛhīāṃ - Bedī, Sohindara Siṅgha Waṇajārā (Nais̱anala Buka S̱āpa, 2020)
Study on folk elements in Panjabi literature.
Keywords: Panjabi literature; History and criticism.; Folklore in literature.